PENINGKATAN PEMBELAJARAN FIQH DENGAN METODE DEMONSTRASI - Ibnu Yazid; Suci Midsyahri Azizah; Fitri Wahyuni (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
This study aims to improve fiqh learning using the demonstration method at MAN 3 Magetan. This type of research is a literature review. Literature review research is a process of collecting and critically examining literature, journals, articles, books, and other sources of information. Data collection is by taking journals from Google Scholar. Analysis of the journal results of this literature review uses the critical appraisal method. research results. the conclusion that can be drawn is that the demonstration method can be an effective method in improving the learning of fiqh, especially in helping students understand and apply difficult concepts. However, it should be noted that the demonstration method must be used judiciously and in the right context to ensure its effectiveness in enhancing the learning of fiqh..